2010
DOI: 10.1128/iai.01070-09
|View full text |Cite
|
Sign up to set email alerts
|

The Lyme Disease SpirocheteBorrelia burgdorferiUtilizes Multiple Ligands, Including RNA, for Interferon Regulatory Factor 3-Dependent Induction of Type I Interferon-Responsive Genes

Abstract: We recently discovered a critical role for type I interferon (IFN) in the development of murine Lyme arthritis. Borrelia burgdorferi-mediated induction of IFN-responsive genes by bone marrow-derived macrophages (BMDMs) was dependent upon a functional type I IFN receptor but independent of Toll-like receptor 2 (TLR2), TLR4, TLR9, and the adapter molecule MyD88. We now demonstrate that induction of the IFN transcriptional profile in B. burgdorferi-stimulated BMDMs occurs independently of the adapter TRIF and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 50 publications
5
38
2
Order By: Relevance
“…5). This is consistent with previous studies showing that type I IFN-responsive gene induction following stimulation of bone marrow-derived macrophages with B. burgdorferi was MyD88, TRIF, and Nod2 independent but IRF3 dependent (27), although a role for Nod2 was suggested by others (41). Furthermore, studies with human cells have suggested a role for various TLRs in B. burgdorferi-induced IFN production (42,43).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…5). This is consistent with previous studies showing that type I IFN-responsive gene induction following stimulation of bone marrow-derived macrophages with B. burgdorferi was MyD88, TRIF, and Nod2 independent but IRF3 dependent (27), although a role for Nod2 was suggested by others (41). Furthermore, studies with human cells have suggested a role for various TLRs in B. burgdorferi-induced IFN production (42,43).…”
Section: Discussionsupporting
confidence: 81%
“…Infection with B. burgdorferi also induces TLR2-dependent and -independent IFN-␤ production by bone marrow-derived macrophages (26). Indeed, much of its production after B. burgdorferi infection appears to be induced independently of MyD88 and TRIF signaling (27). Together the data indicated that type I IFN is strongly induced by B. burgdorferi infection but might be induced independently of TLR signaling.…”
Section: Resultssupporting
confidence: 48%
“…Our findings that TRIF is necessary for induction of type I interferons downstream of B. burgdorferi are in contrast to the findings published by Miller et al (38). While there was an effect of TRIF deficiency on IL-6 secretion in response to B. burgdorferi stimulation, they did not observe an effect on interferon-inducible gene expression in TRIF-deficient cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Bacteria can elicit type I IFNs either by activating TLRs (11,12) or through TLR-independent recognition of bacterial pathogenassociated molecular patterns (PAMPs) within the host cell cytosol (11,18). We and others have begun to demarcate the pathways by which live Bb induces type I IFNs in both mouse and human cells (7,(19)(20)(21)(22). Miller et al (20) demonstrated that live Bb induces transcription of several ISGs in bone marrow-derived murine macrophages (BMDMs) independent of both MyD88 (20) and TRIF (21) yet requiring the transcription factor IFN regulatory factor (IRF) 3.…”
mentioning
confidence: 99%